Abdominal mucormycosis in a child: a case report - Oliveira,Felipe Rezende Caino de (2016)
Abstract A 2-year-old Brazilian female child from the countryside in Bahia State presented with pain in the right flank of the abdomen, accompanied by a daily fever for about 2 weeks before admission. A large mass in the abdomen was resected by the surgical team. The biopsies revealed the mass was an intra-abdominal mucormycosis. However, the diagnosis was late, and despite treatment (amphotericin B) initiation, the patient eventually died.